2022
DOI: 10.1002/anie.202211320
|View full text |Cite
|
Sign up to set email alerts
|

Glycan Modulation of Insulin‐like Growth Factor‐1 Receptor

Abstract: The insulin-like growth factor-1 receptor (IGF-1R) is a receptor tyrosine kinase (RTK) that plays critical roles in cancer. Microarray, computational, thermodynamic, and cellular imaging studies reveal that activation of IGF-1R by its cognate ligand IGF1 is inhibited by shorter, soluble heparan sulfate (HS) sequences (e.g., HS06), whereas longer polymeric chains do not inhibit the RTK, a phenomenon directly opposed to the traditional relationship known for GAG-protein systems. The inhibition arises from smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Further, HS06 was recently found to directly inhibit autoactivation of insulin-like growth factor–1 receptor (IGF-1R), a key cell surface receptor modulating the functions of CSC growth. In contrast, the polymer HS36 was devoid of such an inhibitory effect on IGF-1R . This chain length selectivity is unique and conveys the value in pursuing HS06 as a drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, HS06 was recently found to directly inhibit autoactivation of insulin-like growth factor–1 receptor (IGF-1R), a key cell surface receptor modulating the functions of CSC growth. In contrast, the polymer HS36 was devoid of such an inhibitory effect on IGF-1R . This chain length selectivity is unique and conveys the value in pursuing HS06 as a drug.…”
Section: Discussionmentioning
confidence: 99%
“… 46 More specifically, screening oligosaccharides of different chain lengths (HS02 → HS36) led to the observation that inhibition of colorectal spheroids was highest with HS hexasaccharides, and not as much with tetra- or octa-saccharides. Further, HS06 was recently found to directly inhibit autoactivation of insulin-like growth factor–1 receptor (IGF-1R), 47 a key cell surface receptor modulating the functions of CSC growth. In contrast, the polymer HS36 was devoid of such an inhibitory effect on IGF-1R.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin-like growth factor-1 receptor (IGF-1R) is a receptor tyrosine kinase that plays a key role in abnormal cell growth, tumor invasion, and metastasis and is involved in the development of breast, colorectal, lung, and liver cancers. Short-chain oligosaccharides (HS06) can enter a unique pocket in the IGF-1R ectodomain and compete with the natural cognate ligand IGF-1, thereby blocking the physiological processes mediated by IGF-1R and exerting anti-cancer effects [ 108 ]. Additional studies have shown that HS06 activates p38α/β mitogen-activated protein kinase, followed by inhibition of TCF4 signaling, ultimately inducing apoptosis in cancer stem cells [ 109 ].…”
Section: Various Heparin Conjugates With Non-coagulant Effectsmentioning
confidence: 99%